2019
DOI: 10.1111/eth.12836
|View full text |Cite
|
Sign up to set email alerts
|

Space use patterns of the burrowing echimyid rodent,Clyomys laticeps

Abstract: Space use patterns of a population are a result of the set of movements of its individuals, which are directly influenced by their attributes and environmental conditions. Understanding space use patterns and its determinants may give us insights about a species’ ecology, social and mating systems. Although echimyid rodents display a variety of mating and social systems, movements of burrowing species are poorly studied due to their cryptic habits. Hence, in this study, we evaluated the effects of body mass, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 70 publications
0
15
0
4
Order By: Relevance
“…Reinforcing the idea that C. laticeps is solitary, proposed by Ferrando et al . (), only a single individual was trapped in each of the five burrow systems. These individuals were released near the place of capture, and were further recaptured in different burrow systems.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reinforcing the idea that C. laticeps is solitary, proposed by Ferrando et al . (), only a single individual was trapped in each of the five burrow systems. These individuals were released near the place of capture, and were further recaptured in different burrow systems.…”
Section: Methodsmentioning
confidence: 99%
“…Description of burrow architecture may help to understand their occupancy, because burrow complexity, size of burrow entrances and number and width of tunnels, along with other attributes, may determine species composition and diversity of the commensal fauna (Mukherjee et al, 2017). Reinforcing the idea that C. laticeps is solitary, proposed by Ferrando et al (2019), only a single individual was trapped in each of the five burrow systems. These individuals were released near the place of capture, and were further recaptured in different burrow systems.…”
Section: Data Collectionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is found in open areas of Cerrado and Pantanal biomes, and occurs in grassland habitats in central Brazil and Paraguay (Bezerra & Bonvicino, 2015). It has semi-fossorial habits and sexual size dimorphism, with males having a larger body mass and daily home range than females (Ferrando et al, 2019). A recent study suggested that spiny rat burrows are occupied by a single individual of this species, indicating that they are solitary, and also that this species has non-seasonal, year-round reproduction, and a polygynous mating system (Ferrando et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has semi-fossorial habits and sexual size dimorphism, with males having a larger body mass and daily home range than females (Ferrando et al, 2019). A recent study suggested that spiny rat burrows are occupied by a single individual of this species, indicating that they are solitary, and also that this species has non-seasonal, year-round reproduction, and a polygynous mating system (Ferrando et al, 2019). Spiny rats are considered mainly as frugivore-herbivores, acting both as predators and dispersers of seeds of palms (Bezerra & Bonvicino, 2015), although insect fragments have been frequently recorded in their stomachs (Ferrando, pers.…”
Section: Introductionmentioning
confidence: 99%